Assessment Practices in Costa Rican Mathematics Teachers: Prácticas evaluativas de docentes de matemática costarricenses - Díaz Gutiérrez, Elizabeth (2024)
Over a decade ago, an educational reform was carried out in Costa Rica that included Mathematics Curricula. Problem solving was conceived as the spearhead that should guide pedagogical mediation. The research arises from the need to know, analyze and understand teachers’ assessment practices in light of the theoretical framework of the curricular proposal. This is a qualitative study that seeks, from the phenomenological method; an approach to the reality of the participating people and their daily actions in the field. For data collection were consulted experts in the area, material was documented, and Mathematics teachers and their respective students were included.